2023
DOI: 10.47626/2237-6089-2021-0298
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor serum levels following ketamine and esketamine intervention for treatment-resistant depression: secondary analysis from a randomized trial

Abstract: Objectives Evidence suggests that ketamine’s influence on brain-derived neurotrophic factor (BDNF) might be involved in its mechanism of rapid antidepressant action. We aimed to evaluate the differential impact of ketamine and esketamine on serum BDNF levels and its association with response patterns in treatment-resistant depression (TRD). Methods Participants (n = 53) are from a randomized, double-blind clinical trial comparing the efficacy of single-dose ketamine (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Additionally, regarding the neurobiological basis for ketamine’s rapid antidepressant effects, some studies point to a neurotrophic hypothesis, in which increased expression of brain-derived neurotrophic factor in the medial prefrontal cortex and hippocampus lead to increased synaptic activity in these areas 65 . Data about BDNF and ketamine in humans is still controversial, however 66 . It is worth noting that early evidence points to similar mechanisms for the rapid antidepressant effects of serotonergic psychedelics, such as psilocybin and LSD 67 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, regarding the neurobiological basis for ketamine’s rapid antidepressant effects, some studies point to a neurotrophic hypothesis, in which increased expression of brain-derived neurotrophic factor in the medial prefrontal cortex and hippocampus lead to increased synaptic activity in these areas 65 . Data about BDNF and ketamine in humans is still controversial, however 66 . It is worth noting that early evidence points to similar mechanisms for the rapid antidepressant effects of serotonergic psychedelics, such as psilocybin and LSD 67 …”
Section: Discussionmentioning
confidence: 99%
“…65 Data about BDNF and ketamine in humans is still controversial, however. 66 It is worth noting that early evidence points to similar mechanisms for the rapid antidepressant effects of serotonergic psychedelics, such as psilocybin and LSD. 67…”
Section: D Bandeira Et Almentioning
confidence: 99%
“…Ketamine-induced increases in BDNF are observed in serum after 1 week ( 126 ) and plasma after 230–240 min ( 127 , 128 ). Depressive symptoms of patients correlated with BDNF plasma levels for up to 72 h ( 128 ), while one found no correlation with mood responses ( 129 ). Other studies have found no differences in BDNF levels in plasma at the same time points despite significant improvements in mood ( 129 133 ).…”
Section: Resultsmentioning
confidence: 97%
“…Depressive symptoms of patients correlated with BDNF plasma levels for up to 72 h ( 128 ), while one found no correlation with mood responses ( 129 ). Other studies have found no differences in BDNF levels in plasma at the same time points despite significant improvements in mood ( 129 133 ). In a genome-wide association study, single nucleotide polymorphisms as well as whole genes involved in BDNF-TrkB signaling were shown to be associated with rapid and sustained antidepressant effects in patients with TRD ( 134 ).…”
Section: Resultsmentioning
confidence: 97%
“…The results showing lower BDNF levels in TRD are slightly intriguing, given that all our patients were medicated, and antidepressants were expected to normalize BDNF levels [ 53 ]. However, no significant differences in serum BDNF levels in TRD patients treated with esketamine or ketamine were reported [ 54 ].…”
Section: Discussionmentioning
confidence: 99%